On the transmutation of the Lions operator to the simplest form - Linchuk, Yu.S. (Reports of the National Academy of Sciences of Ukraine, 2017)
Let α∈C,m∈N,m⩾2, and Lα=dmdzm+αzdm−1dzm−1. We investigate the conditions of equivalence of the Lions operator Lα to simpler operators in subspaces of the spaces of functions analytic in domains. We establish the hypercyclicity and the chaoticity of a class of operators.